AC Corrosion behaviour of aluminium and zinc sacrificial anodes in seawater. (17th February 2022) - Tian, Nianpei; Du, Yanxia; Liang, Yi; Yuan, Xun; Chen, Le
ABSTRACT : In this work, the corrosion behaviour of aluminium (Al) and zinc (Zn) sacrificial anodes under AC interference were studied in 3.5% NaCl solution by AC corrosion simulation experiments, weight loss tests and surface morphology analyses. It was found that AC accelerated the corrosion of Al and Zn, and their corrosion rates increased with the AC current density, besides the localised corrosion of Al was much more obvious than Zn. When the AC current density was 100 A m −2, the uniform corrosion rates of Al and Zn increased to 14.6 and 0.46 mm/year, respectively, which were 34.8 and 1.48 times of the free-corrosion rates of them. Meanwhile, both the uniform and localised corrosion rates of Al increased much more significant than that of Zn under AC interference.